Case Report: Pediatric Renal Sarcoidosis and Prognostic Factors in Reviewed Cases - Klaus, Richard; Jansson, Annette Friederike; Griese, Matthias; Seeman, Tomas; Amann, Kerstin; Lange-Sperandio, Bärbel (Frontiers in Pediatrics, 2021)
Background: Pediatric sarcoidosis is a complex inflammatory disorder with multisystemic manifestations. Kidney involvement in children is rare, and prognostic factors are unknown. Case Report and Methods: We report the case of a 16-year-old girl with multiorgan sarcoidosis and renal involvement. The patient presented with tubulointerstitial nephritis, acute kidney injury (AKI), chest CT disseminated noduli, granulomatous iridocyclitis, giant-cell sialadenitis, and arthralgia. The kidney biopsy revealed non-granulomatous interstitial nephritis. Treatment consisted of initial high-dose methylprednisolone pulse followed by oral prednisolone and methotrexate. Full remission was achieved. In addition, we performed a literature review using PubMed and analyzed data on pediatric renal sarcoidosis cases. Results: We identified 36 cases of pediatric sarcoidosis with renal involvement on presentation and data on the end-of-follow-up glomerular filtration rate (GFR). The data from the literature review showed that renal involvement was slightly more prevalent in males (60%). AKI was present in most of the described patients (84%). Oral prednisolone was used in 35 of 36 cases; in more severe cases, other immunosuppressants were used. We newly identified renal concentration impairment and granulomatous interstitial nephritis as factors with a clear trend toward GFR loss at the end of follow-up, emphasizing the importance of kidney biopsy in symptomatic patients. In contrast, higher GFR at presentation and hypercalcemia were rather favorable factors. According to the identified predictive factors, our patient has a good prognosis and is in remission. Conclusion: The factors indicating a trend toward an unfavorable renal outcome in pediatric sarcoidosis are renal concentration impairment and granulomatous interstitial nephritis at presentation, while a higher GFR is beneficial.